Cooperative Skills Improvement Class VIIIA SMPN 5 Banguntapan Through Mind Mapping Assisted Pair Check - Astuti Wijayanti; Ari Kusdiyanta (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
This Classroom Action Research aims to describe the implementation of cooperative learning model type check-assisted mind mapping to improve cooperative skills of class VIIIA students of SMP Negeri 5 Banguntapan Yogyakarta on odd semester 2018/2019 academic year totaling 32 students. Data collection techniques in this study use observation techniques, questionnaires, and documentation. The results showed that the average cooperative skills in the first cycle were 71.1% increasing to 76.1% in the second cycle